RI 4601 Investigation Of The Huber-Rydalch Manganese Deposits, Tooele County, Utah - Eugene Fry (The National Institute for Occupational Safety and Health (NIOSH), 1949)
The Huber-Rydalch manganese property is in the Erickson mining district of Tooele County, Utah. The district covers the southern part of Simpson Mountains, a block rising abruptly above the surrounding desert floor (fig. 1). The Ruber-Rydalch deposits and other deposits in the Simpson Mountains manganese area were examined by Bureau of Mines engineers during 1940 and 1942 under the strategic minerals program. J. T. Pardee visited the district briefly in 1918. A. E. Granger and A. F. Shride, of the Federal Geological Survey, mapped the geology of the area in 1942 and 1943. The manganese deposits occur as veinlike masses in brecciated fault zones that traverse Cambrian and pre-Cambrian quartzite, quartzite conglomerate, and phyllite. The deposits now exposed near the surface represent the oxidized portions of primary mineralization originally containing rhodochrosite and rhodonite associated with quartz and calcite and small quantities of pyrite, galena, sphalerite, and chalcopyrite. The oxide ore is composed of manganite, pyrolusite, psilomelans, and wad in a gangue of quartz, calcite, and brecciated quartzite.